A combined pool/bilateral dispatch model for electricity markets with security constraints (2011)
The safe operation of the power system is a difficult task for the system operator, which is responsible for its coordination, control and monitoring. In most power systems, security is managed through a multi-stage methodology. In this case, the security criteria are incorporated through additional restrictions that modify the initial dispatch calculation. This article presents a generation dispatch model for competitive electricity markets considering safety restrictions. The proposed methodology combines the generation of pool markets and bilateral contracts with optimal post-contingency power flows coupled in a single dispatch model, which avoids economic inefficiencies that appear in conventional multi-stage dispatches. The proposed model is linear, and as such, it is based on the DC model of the network. A six-bar didactic system and the IEEE RTS – 24 system are used to illustrate the operation and effectiveness of the proposed methodology and to compare it with the basic pool / bilateral dispatch without security restrictions. The results show that the inclusion of security restrictions leads to a more expensive dispatch. On the other hand, it was found that the execution of firm bilateral contracts can lead to congestion problems in the system.